The Benefits, Risks, and Challenges of Get-Tough and Support-Oriented Approaches to Improving School Safety. (December 2019) - Mears, Daniel P.; Montes, Andrea N.; Collier, Nicole L.; Siennick, Sonja E.; Pesta, George B.; Brown, Samantha J.; Blomberg, Thomas G.
Schools have adopted get-tough policies and support-oriented policies, each of which creates not only potential benefits but also potential risks for youth delinquency and education. This article identifies potential benefits and risks of get-tough approaches and support-oriented approaches, respectively, to reduce delinquency. It then identifies challenges that can arise when schools seek to balance both get-tough and support-oriented policies. We illustrate these challenges by drawing on prior scholarship on these policies as well as a process evaluation of a large metropolitan school district's pilot initiative to promote school safety and academic performance by assisting court-involved youth. We argue for developing a stronger empirical foundation for school-based approaches that aim to improve school safety and educational outcomes of youth.